2003
DOI: 10.1136/oem.60.8.e1
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic heart disease among livestock and agricultural workers

Abstract: Background: Agricultural workers are exposed to organic dust containing endotoxins, mites, and moulds. Aims: To compare the occurrence of ischaemic heart disease (IHD) among male and female livestock and agricultural workers with gainfully employed men and women in Sweden. Methods: Male and female livestock and agricultural workers were identified in the Swedish National Censuses of 1970 and 1990 and were followed until the end of 1995. The IHD mortality among the livestock and agricultural workers was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Certain occupational groups have a high exposure to particulate air pollution, for example, silica dust, welding fumes and combustion particles. Elevated risks of acute myocardial infarction have been reported in some particle-exposed occupational groups, for example, chimney sweeps,8 construction workers,9 welders,10 11 miners,12 livestock workers13 and cooks 14. A population-based case–referent study, adjusted for smoking, showed an increased risk for IHD after occupational exposure to combustion particles 15…”
Section: Introductionmentioning
confidence: 99%
“…Certain occupational groups have a high exposure to particulate air pollution, for example, silica dust, welding fumes and combustion particles. Elevated risks of acute myocardial infarction have been reported in some particle-exposed occupational groups, for example, chimney sweeps,8 construction workers,9 welders,10 11 miners,12 livestock workers13 and cooks 14. A population-based case–referent study, adjusted for smoking, showed an increased risk for IHD after occupational exposure to combustion particles 15…”
Section: Introductionmentioning
confidence: 99%
“…This study did not include data on smoking habits, but based on other Swedish data on smoking habits in this and other occupational groups, it could be estimated that correction for smoking habits would have further increased the risk by about 9% in male workers and about 5% in female workers [Sjögren et al, 2003].…”
Section: Re: Occupational Endotoxin-exposure and Possible Health Effementioning
confidence: 99%
“…A Swedish study observed a slightly increased risk of ischemic heart disease (IHD) among male (SMR 1.06, 95%CI 0.95-1.18) and female livestock workers (SMR 1.10, 95%CI 0.98-1.23). This study did not include data on smoking habits, but based on other Swedish data on smoking habits in this and other occupational groups, it could be estimated that correction for smoking habits would have further increased the risk by about 9% in male workers and about 5% in female workers [Sjögren et al, 2003].…”
Section: Re: Occupational Endotoxin-exposure and Possible Health Effementioning
confidence: 99%
“…Adjustment for smoking habits would further increase the risk by about 9% in male workers and about 5% in female workers [Sjögren et al, 2003].…”
mentioning
confidence: 99%